PERBANDINGAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) DAN INKUIRI - Dini Maielfi, Sisri Wahyuni, (Universitas Negeri Malang, 2021)
Effective learning processes have an effect on good learning outcomes. Based on what is observed from student learning outcomes in the teaching and learning process, especially science is still below the minimum completeness level (KKM). This is because the processes that occur in science learning are less meaningful because they have not included students in the process of discovery and generate knowledge from their daily activities, students are not accustomed to solving their own problems and lack of linking teaching materials with students' daily lives. This type of quasi-experimental research with a design from The Static Group Comparison Design is to introduce treatments that are not the same between the two groups